Narrow band-gap donor–acceptor copolymers based on diketopyrrolopyrrole and diphenylethene: Synthesis, characterization and application in field effect transistor. (April 2016) - Zhu, Haoyun; Huang, Wei; Huang, Yuli; Yang, Junwei; Wang, Weizhi
Abstract: Three low band-gap diketopyrrolopyrrole based polymers with varying donor groups of furan, thiophene and phenyl were synthesized and then copolymerized with diphenylethene. We investigate the influence of different donor groups and comonomers on the band-gap and field effect transistors. The efficient synthesis of the diketopyrrolopyrrole based copolymers was clearly characterized by a variety of measurements. Two dimensional Grazing Incident X-ray Diffraction was measured to prove that furan and thiophene based copolymers have ordered edge-on structure. These copolymers exhibited strong π–π stacking and excellent hole mobilities when applied in the electric double layer field effect transistors. The high mobility of 2.36 cm 2  V −1  s −1 with an on/off ratio of 10 3 was achieved. Graphical abstract: We designed and synthesized three diketopyrrolopyrrole based polymers with varying donor groups of furan, thiophene and phenyl and then copolymerized with diphenylethene to achieve high mobility. We also oxidized the comonomer of diphenylethene to prove that flexible and rotatable comonomer plays an important role in lowering the band-gap and increasing the coplanarity. Highlights: We prove the flexible structure of copolymers leads to efficient π–π stacking. 2D GIXRD was measured to prove that copolymers have ordered edge-on structure. The mobility of 2.36 cm 2  V −1  s −1 was achieved by using PFDPP as the active layer.